2022
DOI: 10.1111/aas.14077
|View full text |Cite
|
Sign up to set email alerts
|

Serum concentration of oral midazolam as pediatric preanesthetic medication and factors related to the sedation level

Abstract: Background: Preanesthetic medication is important to eliminate surgical anxiety in pediatric patients and facilitate their smooth transfer to the operating room.Midazolam is the most commonly used preanesthetic medication. However, it has been reported that the sedative effect varies from patient to patient. In this study, the pharmacokinetics of midazolam were examined, and the aim was to assess the factors affecting the quality of sedation.Methods: The participants were children ranging in age from 6 months … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Matsuda et al . [11 ▪ ] recently showed that uncooperative behaviour at induction is not caused by low midazolam serum concentrations but is related to a young age of the child.…”
Section: Premedicationmentioning
confidence: 99%
“…Matsuda et al . [11 ▪ ] recently showed that uncooperative behaviour at induction is not caused by low midazolam serum concentrations but is related to a young age of the child.…”
Section: Premedicationmentioning
confidence: 99%
“…Various drugs and dosage forms may be used as premedication, including oral midazolam and ketamine. 7 Midazolam is currently one the most used premedication drugs in pediatric practice. 8 …”
mentioning
confidence: 99%